Revealing the fundamental essence and tectonic structure of Angkul-angkul architecture through the Delphi method (ARTEKS : Jurnal Teknik Arsitektur, 2025)
As a courtyard gateway imbued with symbolic significance, the angkul-angkul embodies Balinese cultural and spiritual values while offering a distinctive tectonic expression that merits preservation. This study seeks to uncover the essence and underlying tectonic principles inherent in the construction and architectural articulation of the angkul-angkul, with the aim of elucidating its architectural value within the traditional building system and identifying its primary structural components. Employing a qualitative methodology, the research integrates an extensive literature review with the Delphi method to achieve expert consensus and ensure analytical validation. The results indicate that the angkul-angkul manifests a harmonious balance among aesthetic visual identity, tradition-based construction systems, and philosophical meaning. These values are articulated through six principal aspects: form, dimension, structure, spatial configuration, materiality, and ornamentation. Collectively, these six aspects constitute the fundamental basis shaping both the structural integrity and aesthetic expression of the angkul-angkul. Ultimately, the study’s findings establish a structured set of design criteria that can inform and guide future angkul-angkul design practices, ensuring that its ongoing development remains contextually grounded, sustainable, and aligned with local cultural principles.
Keywords: Angkul-angkul; Courtyard gate; Culture; Tectonics; Traditional construction